Warm up intensity influences running performance despite prolonged recovery - Paris, H. L.; Sinai, E. C.; Leist, M. A.; Crain, C. M.; Keller, A. M.; Malysa, W.; Renzullo, S. C. (International Journal of Sports Science & Coaching, 2021)
When competing in road races, runners enter starting corrals long before the starting gun triggers. Athletes consequently must complete warm up routines well in advance of race commencement. To optimize performance readiness warm up intensity may need altered to account for the prolonged time between warm up and performance. This study tested the effectiveness of various warm up intensities on 1600 m run performance given a 20 min separation between warm up and time trial, and assessed the physiological bases for performance outcomes. In a randomized, crossover design, 14 athletic men and women [(age (mean ± SEM) = 22 ± 1 y; V·O2peak = 50.3 ± 2.5 ml·kg-1·min-1] completed three warm up routines (light-, moderate-, or high-intensity warm up), rested for 20 min, and ran a 1600 m time trial. Warm up procedures were evaluated for their influence on performance, blood lactate, V·O2, and alterations to neuromuscular function. Time trial performance was significantly faster (P < 0.03) following a moderate-intensity warm up (6:12 ± 18 min:s·1600 m-1) compared to a light-intensity warm up (6:30 ± 18 min:s·1600 m-1). Performance following the high-intensity warm up (6:18 ± 24 min:s·1600 m-1) fell between the light and moderate conditions. When stratified based on starting lactate concentrations, 1600 m performance was optimized when pre-time trial lactate was 2.0-4.9 mmol·l-1. When a prolonged rest separates warm up exercise from time trial performance, warming up remains efficacious. Optimal warm up intensity may be identified using starting lactate as a gauge for performance readiness.